Fragmented City: International Mobility and Housing in Spain - Parreño Castellano, Juan Manuel; Piñeira-Mantiñán, María José; González Pérez, Jesús (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Habitual statements in academic and journalistic fields on the growing inequality of our cities call for multiple reflections. There are numerous indicators of inequality, and territorial specificities give rise to important and subtle differences. What is less debatable is the spatial expansion of inequality (from more outlying, poorer countries to the most developed ones) and its generalization on all scales (from rural to urban areas, and from large metropolises to small cities). Mobility and housing lie at the root of many of these processes, which are represented by phenomena that are often interconnected, such as gentrification and the elite social classes; impoverishment and immigrants in search of work; and segregation and refugees; among many others. In this book, we try to offer a Spanish-based vision of what we call urban geographies in transition-that is, urban geographies in which the key stages, for the purpose of analysis, are the real estate bubble (1996-2007), the subsequent crisis (2008-2013), and the ensuing recovery (2014-2020), without overlooking the impact of the current COVID-19 crisis on the configuration of a new spatial order in cities.